Morderstwo w miejskim labiryncie - konstrukt kryminalnego Sztokholmu we współczesnej literaturze szwedzkiej = A murder in an urban labyrinth - a construct of criminal Stockholm in contemporary swedish literature - Samsel-Chojnacka, Monika (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In Scandinavian crime fiction, from the moment when the genre appeared, the city and its imagehave played very important roles. In the 20th century, writers such as Stieg Trenter, Maj Sjowall andPer Wahloo were not only masters of Swedish crime fiction but also chroniclers of the vivid life ofthe capital city. They managed to create a mythical image of Stockholm between the 50's and the 70's, which serves as a frame of reference for the transformations which have taken place in the cultural reception of individual quarters and locations in recent times.
Keywords: literatura szwedzka - tematyka - 20 w.; literatura szwedzka - tematyka - 21 w.; powieść kryminalna